Physicochemical and Organoleptic Characteristics of Seasoning from Tempe Hydrolysates using Long Treatment of Fermentation and Proteolytic Enzyme Proportion - Kalisa Mawarni Putri; Sri Winarti; Sri Djajati (Nusantara Science and Technology Proceedings)
Tempeh is a native Nusantara food that is often found in traditional Indonesian markets. Over fermentation, due to unsold, they are called over fermented tempeh resulted in non-optimum utilization. Alternative utilizations that can be used is as a seasoning. The making of seasoning can be done by the hydrolysis technique using the protease enzyme of biduri and papain. This study aimed to determine the effect of fermentation time and the proportion of proteolytic enzyme on the physicochemical and organoleptic properties of seasoning from tempeh hydrolysates. The experimental design used was a factorial pattern CRD with two factors. Factor I is tempeh fermentation time (18 hours and 72 hours), while factor II is the enzyme proportion of biduri and papain (0%: 100%; 25%: 75%; 50%: 50%; 75%: 25%; and 100 %: 0%). The best treatment is 72 hours fermentation duration and the enzyme proportion of biduri and papain (50%: 50%) which produces a seasoning powder with the following characteristics: the degree of hydrolysis 82.32%; dissolved protein 58.85%; moisture 7.89%; water solubility index 0.09 gr/ml; oil absorption 0.78 ml/gr, yield 9.32%, organoleptic to taste 3.93 (savory), aroma 3.40 (somewhat pleasant), and color 1.13 (very white), and glutamic acid content 59, 93 mg/100 gr.